Spatial-temporal dynamic monitoring of Mongolian pine (Pinus sylvestris var. mongolica) based on remote sensing data. Issue 11 (2nd November 2018) - Xu, Dawei; Chen, Baorui; Yan, Yuchun; Sun, Xinbo; Xin, Xiaoping
ABSTRACT: The largest natural distribution of Mongolian pine ( Pinus sylvestris var. mongolica ) in China is in Hulunber, Inner Mongolia autonomous region. The Mongolian pine growing on sandy land has been very important for building green ecological shelters in northern China, and its spatial distribution and dynamic variation were the basis for optimizing the layout. The distribution of Mongolian pine from 1985 to 2015 was obtained in the study area. The results showed that the non-growing season is more conducive to classifying Mongolian pine in the study area. Mongolian pine was mainly distributed in a long north-south-oriented strip, and the distribution area increased from 704.84 km 2 in 1985 to 1309.74 km 2 in 2015. Large spatial variations in Mongolian pine occurred in Ewenki Autonomous Banner and Xin Barag Left Banner, but the characteristics of the change differed among different time periods. The area mainly increased from 1985 to 1995 and from 2005 to 2015 but decreased from 1995 to 2005. The spatial pattern of Mongolian pine changed significantly between 1985 and the other years, the overall fragmentation of the population decreased and human activity gradually increased.